2012
DOI: 10.1089/thy.2010.0333
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Subclinical Hyperthyroidism on Blood Pressure, Heart Rate Variability, and Prevalence of Arrhythmias

Abstract: The study suggests that sHT in comparison to euthyroid status may be associated with a statistically significant but probably clinically insignificant increase of QT interval dispersion, prevalence of VES, elevated nocturnal arterial BP, and changes in HRV. These findings broaden our understanding of the cardiovascular effects of sHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 22 publications
6
55
1
4
Order By: Relevance
“…The high level of subclinical hyperthyroidism in this study shows that similar findings were elicited to those of studies suggesting that iodine supplementation increases predisposition to hyperthyroidism by causing thyroid tissue to acquire autonomy [5][6][7]. Increased predisposition to hyperthyroidism as a result of iodine supplementation also increases the prevalence of diseases associated with the thyroid, such as hypertension [18][19]. In addition, it has been suggested that iodine supplementation due to endemic hypothyroidism increases the incidence of hypothyroidism, rather than treating it, and close monitoring of iodine supplementation has been advised [2,8].…”
Section: Discussionsupporting
confidence: 85%
“…The high level of subclinical hyperthyroidism in this study shows that similar findings were elicited to those of studies suggesting that iodine supplementation increases predisposition to hyperthyroidism by causing thyroid tissue to acquire autonomy [5][6][7]. Increased predisposition to hyperthyroidism as a result of iodine supplementation also increases the prevalence of diseases associated with the thyroid, such as hypertension [18][19]. In addition, it has been suggested that iodine supplementation due to endemic hypothyroidism increases the incidence of hypothyroidism, rather than treating it, and close monitoring of iodine supplementation has been advised [2,8].…”
Section: Discussionsupporting
confidence: 85%
“…Studies have shown that OH and SCH are closely related to a variety of metabolic disorders including obesity, hypertension, dyslipoproteinemia, insulin resistance/diabetes mellitus, and cardiovascular diseases. [15,16,23,24] Many metabolic regulators and adipokines/hepatokines including leptin, adiponectin, resistin, and FGF21 were found to be altered with thyroid dysfunction. [25] …”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that subclinical hyperthyroidism affected nocturnal blood pressure levels. Normotensive patients with subclinical hyperthyroidism showed higher systolic (109.3 7.1 vs 107.1 .7.7 mmHg, P 0.035) and diastolic blood pressure levels at night (66.4 6.6 vs 64.8 6.6 mmHg, P 0.047) 34) . Therefore, both hyperthyroid and hypothyroid states increase blood pressure levels, indicating that euthyroid state is important for the maintenance of appropriate blood pressure levels.…”
Section: Lipid Profilementioning
confidence: 94%